Pemberdayaan Remaja dalam Menghadapi Persiapan Pernikahan di kelas Calon Pengantin (Catin) - Rosalinna, Rosalinna; Astuti, KH Endah Widhi; Sugita, Sugita (Jurnal Pengabdian kepada Masyarakat (ABDIKEMAS), 2023)
Marriage is the beginning of healthy reproduction. The large number of divorce phenomena in teenage marriages and unhealthy pregnancies have increased maternal morbidity and mortality. This Community Service provides religious premarital education, conflict management psychology and healthy pregnancy preparation at the Karanganom Klaten health center. This Community Service uses lecture, question and answer and role play methods which will be completed on 1-3 July 2023. The target is teenage couples who are about to get married. The results of the service were obtained as many as 30 premarital couple participants took part in the Bride and Groom Candidate (Catin) class. It was found that the prospective bride and groom's knowledge before the catin training activity at the Karanganom Community Health Center was found to be 45.01 ± 11.24. After the catin training was carried out, the respondent's knowledge increased by 78.88 ± 12.61. The results of statistical tests show that there is a significant increase in knowledge. This means that youth training in marriage preparation is effective for prospective brides and grooms. This activity can be a community-based pre-marital education option that can be carried out independently or as part of an existing community empowerment initiative, such as a youth posyandu or youth organization.